Protective effect of inhaled corticosteroid on children with asthma with Mycoplasma pneumoniae pneumonia - Wei, Bing; Dang, Yan-Hong; Liu, Xiang-Ping; Li, Miao (Frontiers in Pediatrics, 2022)
Background: This study aimed to determine the differences in the characteristics of Mycoplasma pneumoniae pneumonia (MPP) in children with and without asthma and asthmatic children with MPP with and without inhaled corticosteroid (ICS) therapy in order to determine the risk factors for asthma exacerbation and the effect of regular ICS therapy on asthmatic children with MPP. Methods: Children with MPP were divided into two groups according to whether they had a history of asthma. Children with asthma were further divided into an ICS therapy group and a group without ICS therapy. The clinical characteristics, laboratory test results, and pulmonary images were compared between the children with and without asthma. Differences in the severity of acute exacerbation were compared between the children with asthma in the ICS therapy and without ICS therapy groups. Multivariable logistic regression was used to determine the risk factors for exacerbation of MPP in children with asthma. Results: In children with MPP, the differences in the eosinophil counts; total IgE, C-reactive protein, procalcitonin, and lactate dehydrogenase levels; and fever duration, wheezing, extrapulmonary complications, oxygen saturation <92%, severe pneumonia, pleural effusion, co-infection with other pathogens, and lobar pneumonia between children with and without asthma were statistically significant. Among children with asthma with MPP, those in the ICS therapy group were less likely to experience exacerbation, and exacerbations were less severe than those in the without ICS therapy group. The multivariable logistic regression analysis showed that ICS therapy was an independent protective factor against exacerbation. Conclusions: Among children with MPP, the chance of wheezing was higher in children with asthma than in children without asthma. ICS therapy was a protective factor against exacerbation in children with asthma with MPP.